Sociodemographic disparities in postnatal care coverage at comprehensive health centers in Hamedan City - Maleki, Azam; Soltani, Farzaneh; Abasalizadeh, Maryam; Bakht, Rafat (Frontiers in Public Health, 2024)
Postnatal care (PNC) is a crucial component of continuous healthcare and can be influenced by sociodemographic factors. This study aimed to examine the sociodemographic disparities in PNC coverage in Hamedan City.In this cross-sectional study, we utilized existing data recorded in the Health Integrated System of Hamedan City, located in Iran, from 2020 to 2021. The study population consisted of 853 women who were over 15 years old and had given birth within the past 42 days. The Health Equity Assessment Toolkit (HEAT) software was used to evaluate the socioeconomic inequalities in PNC coverage.Overall, 531 (62.3%) of the women received three postnatal visits. The absolute concentration index (ACI) indicates that women aged 20-35 years, illiterate women, housewives, insured individuals, and urban residents experience a higher magnitude of inequality in PNC coverage.The negative values of the ACI suggest that the health index is concentrated among disadvantaged groups, with educational level inequalities being more pronounced than those related to age.Postnatal care coverage among mothers was relatively adequate; however, sociodemographic inequalities existed in the utilization of PNC services. It is recommended that policymakers make efforts to increase access to PNC services for mothers from low socio-economic groups.